The Effects of Ginger on Gallbladder Motility in Healthy Male Humans - Chuah, Seng-Kee (Korean Society of Neurogastroenterology and Motility, 2011)
BACKGROUND/AIMS: Ginger has been used to treat a number of diseases including those affecting the digestive tract. This study was aimed to investigate the effects of ginger on gallbladder volume and gastrointestinal sensation in healthy male subjects. METHODS: Nineteen healthy male volunteers (age 21.3 ± 3.9 years, body mass index 21.6 ± 1.9 kg/m(2)) were studied on 2 occasions in a double blind randomized crossover design. After ingesting ginger (1,200 mg) or placebo capsules (starch), abdominal ultrasound was used to measure the gallbladder volume (calculated from gallbladder width, depth and diameter) and ejection fraction following a standard test meal. Gastrointestinal symptoms were also recorded at regular intervals by visual analogue scales. RESULTS: There were no differences in gallbladder volume or ejection fraction between ginger and placebo. Abdominal symptoms of bloating, fullness, nausea, discomfort and hunger was not different between the 2 occasions. CONCLUSIONS: Ginger (1,200 mg) may not affect gallbladder ejection fraction and possible relevant abdominal symptoms in healthy male human subjects.